Cassava and the future of starch - Tonukari, Nyerhovwo John (Electronic Journal of Biotechnology, 2004)
The nutritive reserves of cassava is made up of starch, which is one of the most important products synthesized by plants that is consumed as food and used in industrial processes. The currently increasing cassava production will lead to higher amount of starch available making it cheaper for industrial processes, and opening up new markets. There is also abundant capacity in many tropical countries such as Nigeria to increase cassava production.